Determinan Kepatuhan Masyarakat Urban pada Protokol Kesehatan dalam Mencegah Penyebaran Covid-19 di Era Kebiasaan Baru - Nayla Kamilia Fithri; Rizki Amalia; Diah Tika Anggraeni (Universitas Muhammadiyah Semarang, 2022)
Background: The COVID-19 pandemic has changed the way of life. We are facing new challenges, including how to carry out daily life while still making efforts to prevent the spread of the Covid-19 virus. The implementation is to implement the health protocol as much as possible. However, we still do not know much about the rate and determinants of adoption of the recommended health behaviors. Objective: The research objective was to determine the factors that affect public compliance with the Covid-19 health Protokol. Method: The method used in this research is to use a descriptive analytical survey research type with a cross-sectional approach. he population in this study were all people with a sample size of 212 people and were selected using convinience sampling. The data was collected using an online questionnaire for one month. Data analysis used in this study was bivariate analysis using the chi square test. Result: The results showed that there were one factors that had a significant relationship with public compliance with health Protocols, it was attitude (p 0.000), and four factors that had not significant effect on public compliance with health Protokol, namely age (p 0,919), knowlage (p 0,913), gender (p 0.146) and martial status (p 0,900). Conclusion: It is hoped that policy makers can disseminate information about Covid using the right media so that it can increase interaction and attract participants in increasing knowledge, attitudes, motivation and public compliance with the Covid-19 health Protokol.